A comparative study on the effects of intrathecal chloroprocaine alone and with fentanyl or clonidine for infraumbilical surgeries - Arvind Khare; Kavita Jain; Mukut Kanwar; Beena Thada; Veena Mathur; Maina Singh (The Indian Anaesthetists' Forum, 2020)
Background and Aims: Antioxidant- and preservative-free form of 2-chloroprocaine (1%) has been re-emerged as a short-acting local anesthetic for use in spinal anesthesia. This study aimed to compare the effects of intrathecal 2-chloroprocaine (1%) alone or with fentanyl or clonidine used as an adjuvant for infraumbilical surgeries. Materials and Methods: Ninety patients of either sex aged between 18 and 60 years with American Society of Anesthesiologists Grade I or II scheduled for infraumbilical surgeries were randomly allocated into three groups (n = 30). Group C received intrathecal 1% 2-chloroprocaine 5 ml (50 mg) + 0.5 ml normal saline, Group CF received intrathecal 1% 2-chloroprocaine 5 ml (50 mg) + 0.5 ml fentanyl (25 μg), and Group CC received intrathecal 1% 2-chloroprocaine 5 ml (50 mg) + 0.5 ml clonidine (15 μg) diluted in normal saline. The onset and duration of sensory and motor blocks, time for demand of rescue analgesia, hemodynamics, and side effects were observed. Results: The onset of sensory and motor blocks was significantly earlier, and the duration of sensory and blocks and time to demand of rescue analgesia were significantly prolonged in both Group CF and Group CC as compared to Group C. Among Groups CF and CC, the duration of sensory and blocks and time to demand of rescue analgesia were significantly prolonged in Group CC. Conclusion: Intrathecal clonidine (15 μg) proved to be a better alternative to fentanyl (25 μg) used as an adjuvant to 1% 2-chloroprocaine for infraumbilical surgeries.